2019
DOI: 10.4103/jcas.jcas_174_18
|View full text |Cite
|
Sign up to set email alerts
|

Who should carry out skin cancer excisions? A systematic review

Abstract: Background:The incidence of melanoma and nonmelanoma skin cancers is increasing in the United Kingdom. Surgical excision carries the highest cure rates for all skin cancers and is the first-line treatment for melanomas and high-risk nonmelanoma cancers. This is most commonly performed by general practitioners (GPs), dermatologists, and plastic surgeons.Objective:The aim of this study was to identify which health-care professionals achieve the best outcomes following surgical excision of skin cancer lesions.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The requirement for specialist input has decreased steadily over the 7-year period studied, indicating an increase in their confidence and skills. In non-integrated settings, a systematic review showed GPs have significantly worse outcomes for skin cancer excisions than Dermatologists and Plastic Surgeons, with the main reason being a lack of training [25]. Further barriers for GP up skilling identified in a qualitative study include limited time and financial compensation for GPs, and a lack of trust from patients and Dermatologists in GP skills [26].…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for specialist input has decreased steadily over the 7-year period studied, indicating an increase in their confidence and skills. In non-integrated settings, a systematic review showed GPs have significantly worse outcomes for skin cancer excisions than Dermatologists and Plastic Surgeons, with the main reason being a lack of training [25]. Further barriers for GP up skilling identified in a qualitative study include limited time and financial compensation for GPs, and a lack of trust from patients and Dermatologists in GP skills [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, BCCs were more often excised by dermatologists, rather than plastic surgeons, presumably because the former group had improved clinical skills in recognizing and demarcating tumors, preoperatively. [11][12][13] Dermoscopy can increase the diagnostic accuracy for BCC; this technique is increasingly recognized as an important tool for BCC diagnosis, enhancing both sensitivity and specificity when compared to the naked eye. In addition improve diagnostic accuracy, several studies have reported that pre-surgical dermatoscopic margin assessments have improved BCC excision over clinical assessments alone.…”
Section: Discussionmentioning
confidence: 99%